A Novel Numerical Algorithm for Simulation of Initiation, Propagation and Coalescence of Flaws Subject to Internal Fluid Pressure and Vertical Stress in the Framework of General Particle Dynamics - Bi, J.; Zhou, X. P. (Rock mechanics and rock engineering, 2017)
A novel numerical model in the framework of General Particle Dynamics is proposed to simulate the coupling effects of the vertical stress and the internal hydraulic pressure on the stress field around the tips of the flaw as well as the propagation and coalescence of cracks. In this proposed method, interaction among discrete particles is formulated using the virtual-bond method. Fractures of the virtual bonds among particles are determined by the Hoek–Brown damage evolution law of rocks. The fractured virtual bonds can only bear the compressive and frictional behaviors between two particles, while the unbroken virtual bonds can bear the tensile, shear and compressive behaviors. Furthermore, a novel generated particle method is proposed to simulate the flow of fissure water. The numerical results show that the water pressure plays a key role in the stress fields around flaw tips as well as the propagation paths and the coalescence pattern of wing and secondary cracks.